Differences in visible light-induced pigmentation according to wavelengths: a clinical and histological study in comparison with UVB exposure - Duteil, Luc; Cardot-Leccia, Nathalie; Queille-Roussel, Catherine; Maubert, Yves; Harmelin, Yona; Boukari, Fériel; Ambrosetti, Damien; Lacour, Jean-Philippe; Passeron, Thierry (Pigment cell and melanoma research, 2014)
Summary The visible light spectrum is wide, and it can be hypothesized that all the wavelengths between 400–700 nm do not induce the same photobiological effects on pigmentation. We assessed the potential pro‐pigmenting effects of two single wavelengths located at both extremities of the visible spectrum: the blue/violet line (λ = 415 nm) and the red line (λ = 630 nm). We made colorimetric, clinical, and histological assessments with increasing doses of those lights on healthy volunteers. Then, we compared these irradiations to non‐exposed and UVB‐exposed skin. Colorimetric and clinical assessments showed a clear dose effect with the 415‐nm irradiation, in both skin type III and IV subjects, whereas the 630 nm did not induce hyperpigmentation. When compared to UVB irradiation, the blue–violet light induced a significantly more pronounced hyperpigmentation that lasted up to 3 months. Histological examination showed a significant increase of keratinocyte necrosis and p53 with UVB, as compared to 415‐ and 630‐nm exposures.